The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1017/s0960428603000362
|View full text |Cite
|
Sign up to set email alerts
|

THE PHYLOGENY OF TRIBE ZINGIBEREAE (ZINGIBERACEAE) BASED ON ITS (nrDNA) AND trnL–F (cpDNA) SEQUENCES

Abstract: A phylogenetic analysis of the tribe Zingibereae (Zingiberaceae) was performed using nuclear ribosomal DNA (ITS1, 5.8S and ITS2) and chloroplast DNA (trnL (UAA) 5p exon to trnF (GAA)). The tribe is monophyletic with two major clades, the Curcuma clade and the Hedychium clade. Paracautleya, sampled for the first time, comes out as predicted while Caulokaempferia comes out in a different position from that found in another recent study. The genera Boesenbergia and Curcuma are apparently not monophyletic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 23 publications
(34 reference statements)
5
28
0
Order By: Relevance
“…Ecomata (see Figure 3 in this paper, Figure 2 in Chen et al 2015: 344). The phylogeny study also supported that Curcuma and Curcuma-like genera were paraphyletic, which was in conjunction with earlier investigations (Kress et al 2002, Ngamriabsakul et al 2004, Záveská et al 2012. Based on the molecular phylogeny study of Curcuma, Zaveska et al (2012) suggested Curcuma-like genera must be transferred to the genus Curcuma.…”
Section: Discussionsupporting
confidence: 89%
“…Ecomata (see Figure 3 in this paper, Figure 2 in Chen et al 2015: 344). The phylogeny study also supported that Curcuma and Curcuma-like genera were paraphyletic, which was in conjunction with earlier investigations (Kress et al 2002, Ngamriabsakul et al 2004, Záveská et al 2012. Based on the molecular phylogeny study of Curcuma, Zaveska et al (2012) suggested Curcuma-like genera must be transferred to the genus Curcuma.…”
Section: Discussionsupporting
confidence: 89%
“…Hitcheniopsis, this classification based on the position of the spikes. At the same time, present results show a surprisingly high morphological congruence between the pollen grains of Curcuma, which, based on molecular systematics, appears to be polyphyletic (Kress et al, 2002;Ngamriabsakul et al, 2004). However, the similarity of the pollen morphology must not provide unequivocal evidence for phylogenetic relationships.…”
Section: Pollen Morphology In Relation To Taxonomy and Phylogeny Curcumamentioning
confidence: 44%
“…A phylogenetic analysis of the tribe Zingiberaceae was performed using nuclear ribosomal DNA and chloroplast DNA [20]. The study indicated that tribe Zingibereceae is monophyletic with two major clades, the Curcuma clade, and the Hedychium clade.…”
Section: Discussionmentioning
confidence: 99%